Origin and Classification of the Honey Bee (Apis mellifera) - Asmaa Dhow Abdullah Mkhebesh; Najwa Mabrouk Alnajih; Afaf Rajab Hamza (African Journal of Advanced Pure and Applied Sciences, 2026)
The purpose of this study was to investigate the origin and classification of the honey bee (Apis mellifera), attempt to catalog its subspecies, and identify their scientific names, as there is considerable confusion and conflicting opinions on this matter.The classification of the honey bee (Apis mellifera) faces numerous challenges due to the unique population structure, biological characteristics, and the varying accuracy of methods used to distinguish between the subspecies. Additionally, transitional zones exist between subspecies, resulting in gradual changes in characteristics among neighboring types.It is believed that bees descended from wasps belonging to the family Sphecidae. Bees are thought to have first appeared in tropical regions during the Eocene epoch, about 40 million years ago, and subsequently spread from those regions to Western Asia, North Africa, and Europe.Bees are classified into ten or eleven families, comprising approximately 700 genera and about 20,000 species. The honey bee belongs to the family Apidae and the genus Apis, which is its only genus and includes five species: The dwarf bee (Apis florea) The giant bee (Apis dorsata) The eastern (Indian) bee (Apis indica = Apis cerana) The western (honey) bee (Apis mellifera) Some specialists add a fifth species similar to the giant bee, which is Apis laboriosa. Except for the western honey bee, the other species live in the wild and have not been domesticated by humans. The western honey bee (Apis mellifera) adapted to primitive hives in ancient times and later to modern hives. As a result of its natural spread and human-mediated transportation to various geographic regions and environments, it acquired traits and characteristics suited to those areas, leading to the emergence of several subspecies (geographic races), with some sources listing more than twenty subspecies or geographic races.These subspecies or geographic races have been classified according to their geographic distribution into four groups and according to color into three groups. There are differing opinions regarding the origin of the honey bee, the number, distribution, and naming of its subspecies, and whether a geographic race is equivalent to a subspecies or represents a lower rank. It should be noted that some do not adhere to the rules of scientific nomenclature and the principles of animal classification